Construction of the septahydroxylated ABC-ring system of dihydro-β-agarofurans: application of 6-exo-dig radical cyclization. Issue 29 (27th March 2017) - Fujisawa, Hiroki; Ishiyama, Tomochika; Urabe, Daisuke; Inoue, Masayuki
Abstract : The intricate tricyclic system of highly oxygenated dihydro-β-agarofurans was constructed by utilizing 6- exo-dig radical cyclization as a key transformation. Abstract : A synthetic route to the septahydroxylated ABC-ring system of dihydro-β-agarofurans was established. The B-ring was formed by a base-promoted diastereoselective Diels–Alder reaction between 3-hydroxy-2-pyrone and ad -glyceraldehyde-derived dienophile, while the C-ring was cyclized by PhSeCl-mediated etherification. The remaining A-ring was constructed via a 6- exo-dig radical reaction. Selective transformations gave rise to the ABC-ring system1 with nine contiguous stereocenters. The thus obtained1 corresponded to the enantiomer of the densely oxygenated core structure of dihydro-β-agarofurans.